Analisis Yuridis Peningkatan Penanaman Modal Asing Di Kota Batam - Junimart Girsang; Lu Sudirman; Desy Susanti (Fakultas Hukum, Universitas Internasional Batam, 2015)
Since the development of Batam in 1970 until today. Great progress has been achieved so far, by the end of 2013, Batam has accumulated a total of about US 16.47 billion. However, the increase in foreign investment in Batam do not necessarily make Batam as the main destination of foreign investment. Indonesia Investment Coordinating Board (BKPM) set a best of seven provincial investment sector